Isolated meningeal myeloid sarcoma with recurrent MLL-AF6 translocation: a case report. Issue 3 (March 2023) - Wang, Chunyan; Zhu, Li; Liu, Songya; He, Cheng; Yi, Shujuan; Wang, Ying; Meng, Fankai; Xiao, Min; Zhang, Yicheng; Mao, Xia
This study aimed to help improve the diagnosis and treatment of isolated myeloid sarcoma. We report the case of a female adolescent patient with isolated meningeal myeloid sarcoma. She was admitted to our department because of vomiting, headache and hearing loss. Positron emission tomography-computed tomography and brain magnetic resonance imaging showed multiple intracranial space-occupying lesions. A complete examination, including morphology, cytology, immunophenotyping, cytogenetics and molecular biology tests of cerebrospinal fluid and bone marrow, was conducted. The diagnosis of primary myeloid sarcoma of the central nervous system with mixed lineage leukemia gene rearrangement with AF6 was established. The patient underwent systemic chemotherapy and intrathecal treatment followed by whole-brain radiotherapy. She achieved complete remission for 84 months and has not developed bone marrow involvement during follow-up. The combination of morphology, cytology, flow cytometry, cytogenetics and molecular analysis can improve the definite diagnosis of isolated myeloid sarcoma.